RANCANG BANGUN ALAT PRES BODY PLAT PADA BENGKEL LAS KETOK DENGAN MENGGUNAKAN SENSOR ULTRASONIC BERBASIS MIKROKONTROLER ARDUINO UNO - Dahriansah Dahriansah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2021)
Â In the field of industrial society, the role of information technology can not be separated anymore. Currently the technology tools people need a tool that can automatically move on its own with the support of computerized systems. With the computerized system, it can provide good service and quickly to internal and external parties.System tool body pressed plates using an ultrasonic sensor is one of a computerized tool that aims to make it easy for users to meet the needs in a range of technology areas, trying to provide tools with a system that automatically and efficiently.This research is expected to be useful for writers as an exercise in designing the tool by using the C programming language and can be used as knowledge and experience. The design of information technology to the shape of the tool body pressed plates using ultrasonic sensor that is made is expected to assist and facilitate the users in the process of its work in the industrial field.